(untitled) (International Journal of Engineering and Computer Science, 2015)
Orthogonal Frequency Division Multiplexing is considered as an advanced communication model which has wide range of applications such as 3G, 4G, and Wi-Fi etc. Though OFDM has lots of advantages over conventional communication models such as FDMA, CDMA still it has some disadvantages in that the major drawback is Peak to Average Power Ratio. In literature several theories are proposed to resolve this issue but none of the algorithm is designed to meet the practical approach. In our work a novel approach is present to resolve the Peak to Average Ratio by introducing the variable slopes parameters K1, K2 and inflexion points A (A>0) and CA (0<C<1) in the probability density function in the Non Linear Companding Transform Technique then based on the inflexion point and variables parameter analysis, The performances of two incompatible features PAPR and Bit Error rate can be achieved. Selection of Non Linear Companding transform parameters plays an essential role as overall performance, robustness depends on it. The proposed theoretical work results can be view through MATLAB simulation.